Contemporary Islamic Education Perspectives of Ibn Sina and Zakiah Darajat: Pendidikan Islam Kontemporer Perspektif Ibnu Sina dan Zakiah Darajat - Mahdany, Diny (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
Islam views education as a means of balancing the physical and spiritual needs of its people. Therefore, Islamic education is an effort to create and shape a better and more meaningful human being in the life of the world and prepare him for life in the hereafter. Although Islamic education as a discipline is recognized as a subject of research and arouses interest among students who want to study it more seriously, this discipline has experienced a rapid decline compared to many other fields of Islamic studies. This type of research is library research, the primary source of material in this study is a paper by Ibn Sina and Zakiah Darajat related to contemporary Islamic education, and the analysis in this study uses deductive descriptive analysis techniques. The results of this study include: a) the main concept used by Ibn Sina is reason, this is because it is influenced by the science of philosophy; b) the main concept used by Zakiah Darajat is mental health which is influenced by psychology; c) the purpose of Islamic education according to Ibn Sina and Zakiah Darajat is a society that has readiness to live in the world and the hereafter by having a balance of knowledge that is flexible, innovative, and creative.